Establishing childhood disability clinics may help reduce the prevalence of disability among children in Africa: A viewpoint - Auwal Abdullahi; Thomson W. L. Wong; Shamay S. M. Ng (Frontiers Media S.A., 2022)
Globally, there are about a billion people comprising of about 95 million children who experience disability. The number of people in Africa living with disability is about 80 million people; out of which 10%−15% are children of school age. The causes of disability among these children include epilepsy, vision loss, or hearing loss, cerebral palsy, poliomyelitis, tetanus, cerebrospinal meningitis and malaria. However, these causes of disability are preventable and can be managed with proper care. The aim of this article is to propose the establishment of childhood disability clinics in Africa in order to help prevent or reduce the incidence/ prevalence of disability among children. Some of the mandates of the clinics will be to carry out routine assessment of children for disability, to provide education on disability and strategies for disability prevention to parents and caregivers, to promptly prevent and manage disability or its causes. However, establishing these clinics requires shared commitment of all the stakeholders.